2022
DOI: 10.1177/10600280221108443
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analyses of Longitudinal Studies on Drug Treatments for Gaucher Disease

Abstract: Objective: Gaucher disease (GD) is a rare disorder linked to the absence/deficiency of glucocerebrosidase. GD can be treated by enzyme replacement therapy (ERT) and substrate reduction therapy (SRT). The aim of this systematic review (SR) is to assess the effectiveness of drugs used for GD treatment. Data Sources: Searches were conducted in PubMed and Scopus, in April 2021. The search strategies encompassed the name of the disease and of the drug treatments. Manual search was also conducted. Study Selection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…Although significant progress has been made on these approaches, clinically approved therapies for MPSs were currently limited to HSCT and ERTs (Table 1 ) [ 24 ]. However, two SRT agents are approved for treating type I Gaucher’s disease, another type of LSDs, while treating the CNS symptoms remains an issue [ 25 27 ].…”
Section: Current Therapeutic Approaches To Mpssmentioning
confidence: 99%
“…Although significant progress has been made on these approaches, clinically approved therapies for MPSs were currently limited to HSCT and ERTs (Table 1 ) [ 24 ]. However, two SRT agents are approved for treating type I Gaucher’s disease, another type of LSDs, while treating the CNS symptoms remains an issue [ 25 27 ].…”
Section: Current Therapeutic Approaches To Mpssmentioning
confidence: 99%
“…ERT is widely used as the rst-line treatment and two intravenously administered ERTs have received marketing authorization in the EU, imiglucerase (Cerezyme®) [5] and velaglucerase alfa (VPRIV®) [6]. Both substances have been shown to be safe and effective, leading to improvements in the hematologic and visceral manifestations of GD [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…ERT is widely used as the first-line treatment and two intravenously administered ERTs have received marketing authorization in the EU, imiglucerase (Cerezyme ® ) [4] and velaglucerase alfa (VPRIV ® ) [5]. Both substances have been shown to be safe and effective, leading to improvements in the hematologic and visceral manifestations of GD [6][7][8][9][10][11]. Although ERT cannot reverse pre-existing permanent bone damage, data from clinical trials have indicated that long-term ERT is associated with a reduction in bone crises and bone pain, an improvement in bone mineral density, and a decrease in bone marrow infiltration based on bone marrow burden (BMB) scores [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%